Réponses

2014-01-19T15:09:09+01:00
A= (6x+1)² + (6x+1)(4-5x)
A= (6x+1) (6x+1+4-5x)
A= (6x+1) (x + 5)

Facteur commun : (6x+1)

B= 6(5x+2) - (x+8)(5x+2)
B= (5x+2) (-x - 8 +6)
B= (5x+2) (-x -2)

Facteur commun : (5x+2)

C= (9-x) (7x+1) - (7x+1) (2-4x)
C= (7x+1) (9-x-2+4x)
C= (7x +1) (3x-11)

Facteur commun : (7x+1)

D= 2x + x(8x-7)
D= x(2+8x-7)
D= x(8x-5)

Facteur commun : x
2014-01-19T15:23:16+01:00
A) (6x+1)²+(6x+1)(4-5x)
     (6x+1)  ( (6x+1)+(4-5x))
     (6x+1) ( 6x+1+4-5x)
     (6x+1)  ( x+5)

b) 6(5x+2)-(x+8)(5x+2)
   (5x+2) ( 6-(x+8))
   (5x+2) ( 6-x-8)
   (5x+2) ( -2-x)

c) (9-x)(7x+1)-(7x+1)(2-4x)
   (7x+1) ((9-x)-(2-4x))
  (7x+1) ( 9-x -2+4x)
   (7x+1) ( 7+3x)

 pour la d) je ne suis pas sûre
d) 2x+x(8x-7)
   x( 2-8x+7)
   x ( 9-8x)